USULAN PERBAIKAN PERENCANAAN DAN PENGENDALIAN PERSEDIAAN DENGAN MEMBANDINGKAN MODEL Q DAN MODEL P PADA PT. XYZ - DIPUTRA, DIZHAR - (Jurnal TIN Universitas Tanjungpura, 2017)
PT. XYZ the one distributors of beverage products Sosro need to reorganize the supply of products, so that’s not the case merits and demerits of the product inventory in the warehouse, and can meet the demand of consumer. Warehouse supplies are affected problems not stable consumer demand and management off warehouses has not been good enough. The determination of a target that has not been as well one of the causative factors of the advantages and disadvantages of the goods. The purpose of this research is to know the cause of the occurrence of excess and shortage of supplies of goods and acquire systems supplies of goods in the warehouse more efficiently with the right methods, but still able to meet customer demand. Based on the results of the research that has been done the total fare demand real model Q lost sales is Rp 8.502.762.354 / yeard and model P lost sales with larger total cost Rp 8.589.222.421 / year. The calculation of the total cost of the total fare sales targets with the model Q lost sales is Rp 13.327.457.160 / year, and model P lost sales with larget total cost Rp 13.435.251.020 / year. Model Q lost sales is a model that has alower total cost than model P lost sales either to demand real and sales targets. Keywords-Inventory, Lost Sales, Model Q, Model P